PERAN HIMPUNAN MAHASISWA MELALUI KEGIATAN PGSD MENGABDI SEBAGAI BENTUK PENGIMPLEMENTASI TRI DARMA PERGURUAN TINGGI DI DUSUN DUNRU KABUPATEN BONE - Muhammad Ikhsan Sukaria; Awaluddin Muin; Sitti Rahmi; Andika Marsuki; Gita Ramadhani (Jurnal Abdi Masyarakat Pendidikan, 2026)
The PGSD Mengabdi program is a community service activity carried out in Dunru Hamlet, Pattinggi Village, Patimpeng District, Bone Regency on January 6-15, 2026 with the aim of improving the quality of education, social, and public health. This activity uses a participatory method through the stages of planning, location survey, proposal preparation, implementation, and post-activity. The results of the activity showed an increase in student participation and motivation to learn through varied learning, increased public awareness of environmental cleanliness through social activities, and increased public awareness of the importance of health through examination and education. The support of external partners also strengthens the implementation of the program. Although there are still limitations in time and facilities, this program has a positive impact and requires continuous follow-up so that the benefits can be felt in the long term